The widow [large type] - Barton, Fiona (Center Point Large Print, 2016)
There's a lot Jean hasn't said over the years about the crime her husband was suspected of committing. She was too busy being the perfect wife, standing by her man while living with the accusing glares and the anonymous harassment. Now she's a widow, and there's no reason to stay quiet. There are people who want to hear her story. They want to know what it was like living with that man. They want the truth-- but the one lesson Jean has learned in the last few years is that she can make people believe anything....